2013
DOI: 10.1002/chem.201203900
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐Linking Density and Temperature Effects on the Self‐Assembly of SiO2—PNIPAAm Core–Shell Particles at Interfaces

Abstract: SiO2-PNIPAAm core-shell microgels (PNIPAAm=poly(N-isopropylacrylamide)) with various internal cross-linking densities and different degrees of polymerization were prepared in order to investigate the effects of stability, packing, and temperature responsiveness at polar-apolar interfaces. The effects were investigated using interfacial tensiometry, and the particles were visualized by cryo-scanning electron microscopy (SEM) and scanning force microscopy (SFM). The core-shell particles display different interfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 48 publications
(89 reference statements)
0
10
0
Order By: Relevance
“…Recent progress in use of “smart” multi-responsive microgels as central component of advanced, functional colloidal materials for controlled drug delivery14 systems and sensors2731 illustrates the importance and the need of further research in this direction 9. In many cases, temperature-responsive poly( N -isopropylacrylamide) (PNIPAM) acts as a microgel scaffold, which exhibits a VPTT (volume phase transition temperature) in aqueous environment within a narrow temperature range around 32 °C, close to body temperature 26,32…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress in use of “smart” multi-responsive microgels as central component of advanced, functional colloidal materials for controlled drug delivery14 systems and sensors2731 illustrates the importance and the need of further research in this direction 9. In many cases, temperature-responsive poly( N -isopropylacrylamide) (PNIPAM) acts as a microgel scaffold, which exhibits a VPTT (volume phase transition temperature) in aqueous environment within a narrow temperature range around 32 °C, close to body temperature 26,32…”
Section: Introductionmentioning
confidence: 99%
“…The most interesting feature that puts microgels in the category of “smart materials” is their unique capability to adjust their dimensions in response to external stimuli, such as temperature, pH, ionic strength, and solvent quality [2,5,6,7,8,9]. Their excellent colloidal stability, ease of synthesis, and post-modification, large surface area enabling encapsulation of the desired cargo makes them potential candidates for antifouling coatings, drug and gene-delivery, tissue engineering, catalysis, water purification, cosmetic applications, and responsive macroscopic materials [10,11,12]. Several review articles can be found in the literature dealing with different fundamental aspects of microgels and the readers are referred to them for detailed information [13,14,15,16,17,18,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Equation is an attractive alternative to eq because measurement of the surface (interfacial) tension of a nanoparticle-laden interface is much more straightforward than direct measurement of the contact angle of adsorbed nanoparticles. A number of recent studies have reported the steady state interfacial tension of nanoparticle-laden fluid interfaces. Using data from these studies, |Δ E | computed from eq is plotted in Figure . Evidently, nanoparticle adsorption at fluid interfaces is irreversible in the majority of cases, given that the magnitude of Δ E delineating reversible and irreversible adsorption lies in the range 20 to 50 k B T .…”
Section: Introductionmentioning
confidence: 99%